Formation and Mechanism Enterprise Development Strategy that Based on Taxes Policy (Economic journal of Lesya Ukrainka Volyn National University, 2015)
The concept of strategic planning is a paradigm of enterprise management nowadays. The article presents the methodological approaches and practical recommendations on the formation and construction of an effective development strategy based on the tax policies of enterprises. Describe how model of strategy consequences for the economy.Enterprise development strategy based on tax policy transformed the running costs of the enterprise in capital investments, wish using the opportunities tax policy and getting positive economic impact, not only enterprise, but for the whole society.Substantiated the main reasons that make it impossible to implement a strategy, first of all, the formation of public opinion on tax evasion and liberal attitude towards and promotion of such information, and the second is the shadow economy, which arises as a result of the first and becomes reason illegal economy and negative business climate
Keywords: tax policy, business strategy, development strategy, tax optimization, minimizing taxes, tax evasion, impeccable business reputation